Diagnosis and epidemiological investigation of an outbreak of Clostridium perfringens food poisoning - Sanz, Juan Carlos; Domínguez, María Felicitas; Sagües, María Jesús; Fernández, Marisa; Feito, Ricardo; Noguerales, Rosa; Asensio, Angel; Fernández De La Hoz, Karoline (Enfermedades infecciosas y microbiología clínica, 2002)
Clostridium perfringens is a classical agent of food-borne disease but because of the mildness and self-limiting nature of the illness, many cases are undiagnosed. This study describes the investigation of an outbreak of diarrhea due to C. perfringens in a public restaurant. An epidemiological survey was performed and the restaurant was inspected. The specific attack rates for the items on the menu were calculated. Odds ratios were calculated to investigate the independent association between each item and the disease using a logistic regression model. Investigation of C. perfringens toxin in the feces of four symptomatic subjects and one exposed but asymptomatic subject was performed by the reverse passive latex agglutination test. The overall attack rate was 70.8%. The main symptoms were diarrhea (100%) and abdominal pain (94%). Significant differences were found in specific attack rates for consumption of different menu items. However, the independent contribution of each item was significant only for consumption of "ravioli with cheese sauce". Fecal detection of C. perfringens enterotoxin was positive in the four symptomatic subjects and negative in the exposed but asymptomatic subject. The overall attack rate in this outbreak was high. The clinical symptomatology was similar to previously published data. The epidemiological analysis revealed "ravioli with cheese sauce" to be responsible for transmission of the disease and clinical investigation together with the fecal enterotoxin detection established C. perfringens as the etiological agent.